Investment guarantees in the crude oil halftone sector in Iraq Analytical legal study - شبيب كاظم مطشر (Journal of Petroleum Research and Studies, 2022)
The legal guarantees granted by States to investors in the oil sector is one of the most important pillars of attracting these investments in various forms and types، bringing capital and the transfer of technology and technical and technical expertise، which contributes to the economic development of these countries and thus develop the infrastructure of the national economy، A suitable legal system for this type of investment. Securing the needs of oil derivatives and achieving self-sufficiency in Iraq did not receive enough attention from the oil refining sector. The public sector is still unable to meet all the requirements of the local market for oil derivatives. The Iraqi government has only a few refineries which are not keeping pace with the global development in this field. Which requires encouraging the private sector to invest in field of liquidating crude oil by granting it a number of advantages and guarantees in order to contribute to meet the needs of the local market on the one hand، and export these products to the international market on the other hand.